Impact of the population size of the earthworm Eudrilus eugeniae (Kinberg) on the stabilization of animal wastes during vermicomposting - Coulibaly, Sifolo S. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
The number of earthworms necessary for the reliable stabilization of four animal wastes (chicken, cow, sheep and pig) was studied by mineralizing 1 kg of each waste with 5, 10, 15 and 20 individuals of the African nightcrawler earthworm (Eudrilus eugenia Kinberg). Total organic carbon (C), total nitrogen (N), C:N ratio, pH, total potassium and total available phosphorus (P) were measured at 0, 30, 60 and 90 d of vermicomposting. The cocoons and hatchlings produced by the earthworms were also investigated. The pH approached the acidic level during the vermicomposting of cow, sheep and chicken wastes and shifted to neutral in pig vermicompost. K content, total organic C and the C:N ratio decreased during vermicomposting when N and P content increased in the four animal wastes. Cow, sheep and chicken wastes were well stabilized in the treatments with 10, 15 and 20 earthworms after 90 d when pig waste was converted into a value product in the treatments with 15 and 20 earthworms. At the end of the experiment, there was a similarity respectively in N content and C:N ratio between 10, 15 and 20 earthworms for cow, sheep and chicken wastes and between 15 and 20 individuals of E. eugeniae for pig waste. Chicken waste had the greatest number of hatchlings and biomass, followed by cow, sheep and pig wastes at the end of the experiment. The greatest number of cocoons was collected in pig waste. Results of this study may help in the formulation of a strategy for vermicomposting with E. eugeniae.